Confucius' Role in the Development of China Today: 孔子在当今中国发展中所扮演的角色 - Rudiansyah, Rudiansyah; Guizhi, Kou (Mandarinable: Journal of Chinese Studies, 2023)
The study of China in Indonesia has never ceased; the study itself is always fascinating. China is unique both in terms of language and culture. The title 'The Role of Confucius in the Development of China Today' was chosen to examine and understand how China has developed itself through the influence of Confucius. To realise the Chinese dream, China's traditional cultural heritage is a fundamental force that cannot be ignored. The values of Confucius have been the basic norms of Chinese society for a long time, although they were restricted and banned during the Cultural Revolution (1966-1976) as a result of the movement to abolish old values, and have now been revitalised, in parallel with the establishment of Confucius Institutes in many countries around the world.